The power of top members is related to the performance of crawl swimming in adolescents swimming athletes (Research, Society and Development, 2022)
Introduction: To optimize the performance of young swimming athletes it is important to understand the swimming optimization mechanism. Objective: To verify the relationship between upper limb power and 50-m crawl swimming performance in school swimming athletes of both sexes. Method: Cross-sectional study, with a sample of 20 school swimming athletes (age: 12.7 ± 0.8, 50% male and 50% female). We analyzed the performance of crawl swimming through a maximum sprint of 50 m, performed in an Olympic swimming pool. We analyzed the power of upper limbs through the medicineball throwing test, the unit of measure of the upper limbs test was converted into watts through a Newtonian physics equation. Through correlation and regression analysis, we verified the relationship and contribution of upper limb power to the 50-m crawl swimming performance. Results: Upper limb power was related to the performance of swimmers of both sexes (Male: r = -0.77, p = 0.009. Female: r = -0.68, p = 0.0007). In addition, it pointed out the ability to predict the performance of swimmers of both sexes (Male: r² = 0.593, β = -0.32, p